Life cycle assessment of the tiny house initiative in the United Arab Emirates - Sabobeh, Lara; Al Hassani, Rabab; Alomar, Laila; Atabay, Serter; Mortula, Md Maruf; Ali, Tarig A.; Taher, Aqeel Mohammed (Frontiers in Sustainable Cities, 2024)
IntroductionThere has been a significant increase in global energy usage due to urbanization and population growth. The built environment is responsible for over one third of global energy consumption, carbon dioxide emissions, and over a quarter of greenhouse gas emissions. The United Arab Emirates building, and construction sector consumes 70% of the entire country’s electricity demand and uses large amounts of raw materials, accelerating resource scarcity. The tiny house offers several environmental and sustainability benefits that have contributed to its growing popularity.MethodsIn this study, the environmental impacts of a tiny house, built on the American University of Sharjah campus will be evaluated using life cycle impact assessment. A cradle-to-grave evaluation was conducted for the life cycle assessment of the tiny house, with a functional unit of 1 m2, using the ReCiPe 2016 V1.03 midpoint method.ResultsThe environmental impact associated with the production and operational phases was most severe, aligning with similar studies on residential buildings. In the material production phase, concrete and steel had the most significant environmental impacts, particularly in the climate change category. These results highlight the importance of focusing on sustainable innovations in material production and recycling to mitigate environmental impacts. The operational phase contributed to approximately 77% of the total carbon dioxide emissions over the 50-year lifespan of the tiny house, primarily due to energy consumption for heating and cooling.DiscussionWhile the findings align with previous studies on residential buildings, it is important to consider the context of a tiny house; its small size results in a significantly lower overall environmental impact compared to larger homes.